MANAJEMEN TRAFIK MENGGUNAKAN HTB UNTUK MENINGKATKAN KUALITAS LAYANAN IP NETWORK: Traffic Management Using HTB to Improve IP Network Service Quality - Bayu Widodo (IPB University, 2021)
ABSTRACTIn IP-based networks with many users, a bandwidth usage regulation mechanism is needed to ensure service quality. Mikrotik RouterOS has a feature to run QoS known as queue. RouterOS uses the Hierarchichal Token Bucket (HTB) method as the main queue method. The results of the tests carried out show that HTB is able to provide traffic limitation facilities for each classification and guarantee or ensure the amount of bandwidth is less or equal to the predetermined amount. If there is unused bandwidth it can be used by a lower classification (borrowing mechanism).